Medical Complexity Mediates Healthcare Resource Use in the Socially Vulnerable. Issue 3 (May 2022) - Hanlon, Alexandra L.; Pauly, Mark V.; Huang, Liming; Lozano, Alicia J.; Hirschman, Karen B.; McCauley, Kathleen; Press, Matthew; Naylor, Mary D.
SUMMARY: Goal: The objective of this retrospective, observational study was to assess the mediating effect of medical complexity on the relationship between social vulnerability and four acute care resource use outcomes—number of hospitalizations, emergency department (ED) visits, observation stays, and total visits. Such information may help healthcare managers better anticipate the effects of interventions targeted to the socially vulnerable in their patient population. Methods: Electronic health records of 147, 496 adults served by 27 primary care practices in one large health system from 2015 to 2017 were used. Descriptive statistics were applied to characterize patients and the primary care practices included in the study. Causal mediation analyses using a modified Baron and Kenny approach were performed. Principal Findings: Causal mediation analyses demonstrated that increased social vulnerability was associated with increased medical complexity (incidence rate ratio [IRR] = 1.57) and increased numbers of hospitalizations (IRR = 1.63), ED visits (IRR = 2.14), observation stays (IRR = 1.94), and total visits (IRR = 2.04). Effects remained significant, though attenuated, after adjusting for medical complexity (mediator), demographics, and medications (hospitalizations IRR = 1.44, ED visits IRR = 2.02, observation stays IRR = 1.74, total visits IRR = 1.86). Social vulnerability, given medical complexity, explained between 8% (ED visits) and 26% (hospitalizations) of the variation in outcomes. Practical Applications: These findings reinforce the need to modify interventions for medically complex adults to address their social needs and, consequently, reduce costly health services. Health systems seeking to reduce costly care can use these results to estimate savings in the treatment of patients with high social vulnerability—before they get chronic conditions and later as they seek care.